Pengaruh Intangible Asset dan Leverage Terhadap Nilai Perusahaan - M. Aria Gymnastiar; Muhammad Nur Fauzi; Zikratul Ramadhan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine the simultaneous and partial effect of intangible assets and leverage on company value in real estate property companies listed on the Indonesia Stock Exchange in 2020-2021. This research uses quantitative methods. The unit of analysis used is the group, namely property and real estate companies listed on the Indonesia Stock Exchange in 2019-2021 and are the population in this study. By using purposive sampling, 35 companies were selected as the research sample. The data analysis method used in this research is descriptive statistics and panel data regression analysis using Eviews 12 software. The results of this study indicate that intangible assets and leverage simultaneously and partially have a significant positive effect on firm value.